Welcome to the poisoned chalice the destruction of Greece and the future of Europe - Galbraith, James K. (Yale University Press, 2016)
In this fascinating, insightful, and thought-provoking collection of essays-which includes letters and private memos to both American and Greek officials, as well as other previously unpublished material-Galbraith examines the crisis, its causes, its course, and its meaning, as well as the viability of the austerity program imposed on the Greek citizenry. It is a trenchant, deeply felt commentary on what the author calls "economic policy as moral abomination," and an eye-opening analysis of a contemporary Greek tragedy much greater than the tiny economy of the nation itself.